Gambaran Pengetahuan dan Perilaku Pasien Usia 12-45 Tahun Terhadap Penyakit Pulpa Di Puskesmas Minasa Upa - Aulyah, Dwi Rezky; Pariati; Wijaya, Ayu; Usman, Faradillah (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2023)
Dental and oral health is a part of body health that cannot be separated from one another, because dental and oral health will affect overall body health. Dental and oral disease is the most frequently complained about health problem in the world, especially Indonesia. The common dental disease suffered by people is caries which can later progress to pulp disease. This study aims to determine the knowledge and behavior of patients aged 12-45 years regarding pulp disease at the Minasa Upa Community Health Center. The research design used is descriptive research. The population in this study were patients at the Minasa Upa Health Center dental clinic. Sampling used accidental sampling technique. The results of the study showed that the majority of respondents' knowledge was good, namely 27 respondents (60.0%). The conclusion of this study was that the respondents' knowledge of pulp disease was said to be good, namely 27 respondents (60.0%) and the respondent's behavior towards pulp disease was said to be bad, namely 20 respondents. (44.5%) Keywords : Knowledge; behavior; disease; pulp